An Investigation Into the Interplay Between Chinese EFL Teachers' Emotional Intelligence, Ambiguity Tolerance, and Work Engagement - Yang, Nan (Frontiers in Psychology, 2022)
Teachers’ work engagement is regarded as a critical issue in educational contexts, so the emotional factors and personality traits, and their effects on teacher engagement have drawn the attention of investigators. This study seeks to investigate the relationship between teachers’ emotional intelligence, ambiguity tolerance, and work engagement. Moreover, this study tries to investigate the contribution of emotional intelligence and ambiguity tolerance to teachers’ work engagement. To do so, 322 teachers (96 males and 226 females) participated in this study. Schutte’s Self Report Emotional Intelligence Test (SSEIT), Multiple Stimulus Types Ambiguity Tolerance Scale-II (MSTAT-II), and Self-report engagement Questionnaire were used in this study. The statistical techniques used in this study are the Spearman Rho test and ANOVA. The findings showed that there are significant correlations between work engagement, emotional intelligence, and ambiguity tolerance. Comparing the predictability power, teachers’ emotional intelligence (B = 0.611) proved to have a higher index compared to their index of ambiguity tolerance (B = 0.2). This study concluded that emotionally intelligent teachers and teachers with higher levels of ambiguity tolerance are more engaged in the EFL contexts. Moreover, the study has some pedagogical implications and suggestions for different teacher educators, policy-makers, and advisors. The ideas can improve their awareness of teachers’ emotional intelligence, ambiguity tolerance, and work engagement in educational environments.